Auditing and Accountability of Public Funds in Mbale City Council - Mary Musingo (Uganda Christian University, 2024)
The research was undertaken to investigate on auditing and accountability of public funds in Mbale city council. It was guided by three objectives; to find out the effect of risk assessment on accountability of public funds in Mbale city council, to analyze the effect of internal control environment on accountability of public funds in Mbale city council, to assess the effect of auditor's independence on accountability of public funds in Mbale city council. The researcher used a sample size of 63 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective shows that risk assessment positively (Beta=0.153) predicts the financial of public funds in Mbale city council and effect is significant at p-value < 0.05 by 9.6%, Results of the second objective reveals that internal control environment on positively (Beta=0.224) predicts the accountability of public funds in Mbale city council and effect is significant at p-value < 0.05 by 7.7% while results of the third objective show auditor's independence (Beta=0.091) predicts and affects their auditor's independence on accountability of public funds in Mbale city council. However, its effect is insignificant at p-value > 0.05. by 2.1%. It can be concluded that risk assessment has a significant effect on of public funds in Mbale city council, internal control environment has a significant effect on accountability of public funds in Mbale city council and lastly auditor's independence has a significant effect on the auditor's independence on accountability of public funds in Mbale city council. There is need to implement a robust internal control system that includes regular audits, continuous monitoring, and real-time reporting of financial transactions. Integrating advanced data analytics and risk management tools can help identify potential areas of fraud, mismanagement, or inefficiencies early.
Undergraduate research